2012
DOI: 10.1097/lgt.0b013e31825c2e24
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Symptoms, Sexual Function, and Attitudes Toward Counseling of Women Newly Diagnosed With Vulvodynia

Abstract: Women with newly diagnosed vulvodynia report substantial impact of vulvar pain but feel little control over symptoms. Sexual desire and sexual satisfaction are low. Most of the respondents would consider counseling to help address these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Regarding treatment content, the information part of the internet-based treatment was perceived as very important for understanding the bodily reactions associated with chronic pain. Highly educated women with vulvodynia perceive themselves as having very little power to control and understand their symptoms [26]. Patient education could enhance the sense of empowerment and be advantageous for the management of vulvodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment content, the information part of the internet-based treatment was perceived as very important for understanding the bodily reactions associated with chronic pain. Highly educated women with vulvodynia perceive themselves as having very little power to control and understand their symptoms [26]. Patient education could enhance the sense of empowerment and be advantageous for the management of vulvodynia.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this sense of trust facilitates a more detailed description of her vulvodynia symptoms and intimate problems (1,55). It is also found that women with newly diagnosed vulvodynia are open to counselling to address the psychosexual aspects of their vulvar pain, and they report that it has helped them to cope with intimacy problems (56).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggest that there is a need to address the psychosocial aspects of living with vulvodynia in every treatment plan, as many of these patients have depression, anxiety, emotional distress, somatization, irritability, and anger. [11][12][13][14] Additionally, women with vulvodynia tend to have increased difficulty expressing feelings and communicating with their partners.…”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial needs of patients with vulvodynia and their partners have been demonstrated in numerous reports. Multiple studies suggest that there is a need to address the psychosocial aspects of living with vulvodynia in every treatment plan, as many of these patients have depression, anxiety, emotional distress, somatization, irritability, and anger 11–14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation